Creative destruction of the university - Krzysztof Leja; Emilia Nagucka (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
Authors take the issue of change in the modern university. Assuming that the objective of the university is, in addition to the mass education, training the elite of intellectual entrepreneurs (Kwiatkowski, 2000; Kwiatkowski, Sadlak, 2003) - prospective leaders of the knowledge-based society, it is proposed the creative destruction of the university organization, the essence of which is to move the axis of the basic organizational units of the university, such as departments, into teams, and coordination axis of the university move into units. The proposal is embedded in the Schumpeter's idea of creative destruction (Schumpeter, 1960), and refers to the Burton Clark's concept of the entrepreneurial university (Clark, 1998, 2004), the concept of ambidextrous organization (March, 1991, Tushman, O'Reilly III, 1996; Birkinshaw, Gibson, 2004), third generation university by Johan Wissema (2009) and the concept of the knowledge-based university, using the paradigm of knowledge-based organization (Leja, 2011). Additionally, the paper presents the necessary conditions of the proposed change, and the risk associated with it. Authors try to prove, using Gareth Morgan's metaphors (2001, 2005), that the proposed change is the transition from mechanistic - organism university to the university described by metaphors of organisms and self-organization.
Keywords: D23; D83; I23; 330; creative destruction; ambidextrous organization; Schumpeter; university; Morgan